Discovery of an unusual new radio source in the star-forming galaxy M82: faint supernova, supermassive black hole or an extragalactic microquasar? - Muxlow, T.; Beswick, R.; Garrington, S.; Pedlar, A.; Fenech, D.; Argo, Megan; van Eymeren, J.; Ward, M.; Zezas, A.; Brunthaler, A. (Wiley-Blackwell Publishing Ltd., 2010)
A faint new radio source has been detected in the nuclear region of the starburst galaxy M82 using Multi-Element Radio-Linked Interferometer Network radio observations designed to monitor the flux density evolution of the recent bright supernova SN 2008iz. This new source was initially identified in observations made between 2009 May 1 and 5 but had not been present in observations made 1 week earlier, or in any previous observations of M82. In this Letter, we report the discovery of this new source and monitoring of its evolution over its first 9 months of existence. The true nature of this new source remains unclear, and we discuss whether this source is an unusual and faint supernova, a supermassive black hole associated with the nucleus of M82 or intriguingly the first detection of radio emission from an extragalactic microquasar.